INTERNATIONAL PROTECTION AND APPLICATION OF THE NON-REFOULEMENT PRINCIPLE IN COUNTRIES WITH INADEQUATE OR INACCESSIBLE HEALTHCARE - Stojanović, Bojan; Krasić, Bogdan; Stojanović, Zoran (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The coronavirus pandemic has once again exposed dramatic differences between countries in terms of access to and quality of healthcare. The authors analyse whether the endangered right to health, as a basic human right, through inadequate or inaccessible healthcare can be the basis for granting the international protection or applying the principle of non-refoulement, with special reference to the context of the coronavirus pandemic. Theoretically and in legal documents, this topic is insufficiently covered, and case law is still in the process of formation. The current practice of the European Court of Human Rights regarding the right to asylum and health is not uniform, but it is to be expected that the coming period will bring the formation of relevant case law and changes in the legal framework.
Keywords: right to health; asylum; international protection; human rights; migration; pandemic; COVID-19; non-refoulement; European Court of Human Rights